Legal Protection for Intermediaries in Transactions Involving Negotiable Certificates of Deposit: A Comparative Analysis of Indonesian and United States Law - Sution, Enroy; C. , Adam Richard (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Financial market transactions involving negotiable instruments require legal certainty, proportional liability, and reliable protection for parties acting in good faith. Specific Background Negotiable Certificates of Deposit create complex chains of legal relations because they are transferable financial instruments involving issuers, investors, and intermediaries. Knowledge Gap Existing regulation has not clearly defined the legal status, duties, and civil liability limits of intermediaries, causing vulnerability in disputes and inconsistent legal interpretation. Aims This study analyzes intermediary protection in Negotiable Certificate of Deposit transactions through the PT MNC Asia Holding Tbk case and formulates a stronger legal framework through comparison with the United States legal system. Results The findings show that intermediary protection remains partial, reactive, and normatively ambiguous, while the Uniform Commercial Code provides a clearer model through holder in due course protection, good faith standards, transfer warranties, and fault-based liability. Novelty The study offers a comparative legal formulation that recognizes intermediaries as independent transactional actors requiring preventive and repressive safeguards. Implications The findings support specific regulation for negotiable instruments, explicit recognition of intermediary status, national due diligence standards, and adoption of good faith and holder in due course principles to strengthen fairness, legal certainty, and financial market stability. Highlights: Existing rules leave brokers vulnerable to broad liability interpretation. Good faith parties receive clearer safeguards under commercial paper doctrine. Regulatory reform should define duties, status, and due diligence standards. Keywords: Legal Protection, Negotiable Certificate of Deposit, Uniform Commercial Code.